PERLINDUNGAN HUKUM TERHADAP PESERTA BPJS KESEHATAN DI RUMAH SAKIT IBU DAN ANAK ERIA BUNDA KOTA PEKANBARU - Candra, Reynold Maytri; Indra, Mexsasai; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study aims to determine the implementation of legal protection related to the rights of patients of BPJS health participants in obtaining health services and knowing the constraints and efforts of the hospital in implementing health services BPJS Health in at the Mother and Child Eria Bunda Pekanbaru City hospital. The research method used is a descriptive sociological juridical method, where the research data is obtained from field study and library research, the data analysis is done qualitatively.Based on the results of the study, legal protection for BPJS Health participants at the Mother and Child of Eria Bunda Pekanbaru City hospital viewed from the aspect of regulation has not been protected by its rights as service consumers, as a participant of the Health Insurance Agency (BPJS) which has been regulated in the Law on Health Insurance Agency (BPJS), National Social Security System (SJSN) and regulations other related. In its implementation there are still shortcomings, such as lack of information guarantees for the health suffered by BPJS participant patients, lack of guarantees for the safety, comfort and safety of BPJS participants, lack of givingquality health services in accordance with professional standards and operational procedure standards, and the lack of providing guarantees to patients the freedom to claim harmed rights granted by the hospital againstBPJS Health participants which cause the services provided to BPJS Health participant patients are not optimal.There are still obstacles faced by the Eria Bunda Mother and Child hospital and the Health Insurance Agency in providing health services to participants the Health Insurance Agency. however, there have been several efforts made by the Mother and Child Eria Bunda hospital and the Health Insurance Agency to fulfill the rights of participants the Health Insurance Agency including providing quality services according to the standards that have been establisheddetermined according to the needs of patients participating in the Health BPJS, increasing the number of health facilities I as a reference BPJS holders. Provide education, and dissatisfaction of BPJS participants can be done by submitting to the existing Ethics & Law Committeeat the Eria Bunda Mother and Child hospital and can make complaints to the BPJS.Keywords : Legal Protection, Participants of BPJS Health, Hospital